Formação de professores de ciências e educação inclusiva: um olhar para os indicadores sociais das regiões Sul e Sudeste - Lagassi, Paloma Laurea (Universidade Federal de São Carlos, 2020)
One of the topics of great importance for current education is the inclusion of pupils with disabilities and / or special educational needs (SENs), and we must analyze how this process has taken place. Relevant factor for the analysis is the guarantee of enrollment to this portion of students established in our legislations since the Federal Constitution of 1988. The enrollments of these students in regular spaces of schooling have as one of their main challenges the training of teachers to act with the diversity of the student. Thus, this research aimed to analyze the social indicators of the school census on the formation and profile of teachers in the area of Sciences, graduated in degrees in Physics, Chemistry and Biological Sciences, in view of the assumptions of inclusive education. In order to meet this objective, the microdata of the school census was analyzed, considering the information about the initial and continuous training area of these teachers in the perspective of inclusive education. The microdata from the years 2007 to 2017 were analyzed through historical-dialectical materialism, and their discussion was based on the theoretical framework linked to Historical-Critical Pedagogy and Historical-Cultural Theory. The results of this research reveal that there is a very small number of teachers working in the public network who have in their main education subjects focused on attending the SEN or the Brazilian Sign Language (LIBRAS), as well as teachers who have continuing education in Special Education, which did not exceed 0.39% in 2017. Moreover, the analysis of microdata when dealing with teacher hiring shows that precarious and temporary hiring bonds are becoming increasingly naturalized, contributing to greater challenges in the school environment. This research recognizes that although data collection for the school census finds weaknesses, these do not diminish the importance of research that focuses on microdata, since they guide new policies and actions in education, including financing proposals. It is essential, therefore, to know the limitations of the school census database, but at the same time to study it, as it allows us to draw both an overview of enrollments of students with disabilities and / or SEN over the years, how much to understand the characteristics of formation basic education teachers.
Science teacher education and inclusive education: a look at social indicators of South and Southeast regions
Keywords: Inclusão escolar; Indicadores sociais; Formação de professores; Ensino de Ciências; School inclusion; Social indicators; Teacher education; Science teaching; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO